(untitled) (Fiep Bulletin - online, 2014)
Subclinical hypothyroidism (SH) is defined as a condition in which the levels of (TSH) thyrothrophine are elevated , associated to normal levels of the thyroid hormones T4 (thyroxine) and T3 (triiodothyronine) and their respective free functions. Although many studies about these patients group are done, little is known about exercise-recovery heart rate (HR). Objective: Considering the possibility of occurrence of changings in cardiovascular response in this group of patients, this study aims to evaluate the heart rate (HR) response in the three first minutes of exercise-recovery, before and after six months of recovering from the euthyroidism condition, through replacement with levothyroxine. Methods: A total of 17 patients was randomly divided into two groups: treatment (n=9; 43,1 ± 6,6 years) and observation (n=8; 45,5 ± 5,6 years). Patients were submitted to a cardiopulmonary test, performed in a treadmill, using Modified Balke´s protocol, in two moments: basal and after six months of treatment or observation. It was used the Mann-Whitney test to compare the mean values inter groups and to the comparison intra groups after 6 months of intervention or observation it was used the Wilcoxon test (p=0,05). Results: Both groups presented similar mean HR values in the first evaluation. However, when we analyzed results after six months of intervention or observation, we observed that the group that received levothyroxine presented lower values of HR in all minutes of exercise-recovery considered in the present study. The observation group maintained the same mean values of HR. Conclusion: Patients treated with levothyroxine presented a better HR exercise-recovery, especially during the first minute.